Synthesis and biological activity of sulfur compounds showing structural analogy with combretastatin A-4 - Edson dos A. dos Santos; Paulo C. Prado; Wanderley R. de Carvalho; Ricardo V. de Lima; Adilson Beatriz; Dênis P. de Lima; Ernest Hamel; Marzena A. Dyba; Sergio Albuquerque (Química Nova, 2013)
We extended our previous exploration of sulfur bridges as bioisosteric replacements for atoms forming the bridge between the aromatic rings of combretastatin A-4. Employing coupling reactions between 5-iodo-1,2,3-trimethoxybenzene and substituted thiols, followed by oxidation to sulfones with m-CPBA, different locations for attaching the sulfur atom to ring A through the synthesis of nine compounds were examined. Antitubulin activity was performed with electrophoretically homogenous bovine brain tubulin, and activity occurred with the 1,2,3-trimethoxy-4-[(4-methoxyphenyl)thio]benzene (12), while the other compounds were inactive. The compounds were also tested for leishmanicidal activity using promastigote forms of Leishmania braziliensis (MHOM/BR175/M2904), and the greatest activity was observed with 1,2,3-trimethoxy-4-(phenylthio)benzene (10) and 1,2,3-trimethoxy-4-[(4-methoxyphenyl) sulfinyl]benzene (15).